Techniques for qualitative and quantitative determination of drugs of abuse in biologic fluids - Pomilio, A.B. (2006)
A variety of methods have been developed for determination of drugs of abuse in urine, plasm/serum, bilis, hair and others in clinical and forensic samples. Relevance of the application of the technique of gas-liquid chromatography and different types of mass spectrometry are discussed in this paper, being sample preparation emphasized. Amphetamines, cannabinoids, cocaine and benzoylecgonine, morphine and metabolites, phenciclidine, benzodiazepines, tricyclic antidepressants, barbiturates, opiates, local anesthetics and methadone were properly analysed and quantified by means of this methodology. © 2007 Federación Bioquímica de la Provincia de Buenos Aires.